Human Milk Oligosaccharides: The Journey Ahead - Chandan Ray; Joshi A. Kerketta; Subhash Rao; Snehal Patel; Shantanu Dutt; Kamal Arora; Femitha Pournami; Phani Bhushan (International Journal of Pediatrics)
Breast milk is a complex biological fluid that is rich in nutrients and bioactive agents that support the healthy growth and development of the newborns. Human milk oligosaccharides (HMOs) are unconjugated glycans that constitute an important component of the protection conferred by breast milk on the neonate. HMOs may act locally on the neonatal intestine by acting as signalling molecules and directly interacting with the host cells. Although fucosylated and sialylated HMOs have little nutritional value, they exert important prebiotic as well as immunomodulatory effects on the infant gut. However, there is heterogeneity in the quantity and quality of HMOs in breast milk produced by mothers under influence of the genetic and environmental factors. This review encompasses the salient aspects of HMOs such as composition, function, structural diversity, and functional impact on the growth and survival of newborns. In this review, the current knowledge on HMOs is contextualised to discuss the gaps in scientific understanding and the avenues for future research.